Highly tunable actuation and mechanical properties of 4D-printed nematic liquid crystal elastomers. (July 2022) - Siddiqui, Z.; Smay, J.; Azoug, A.
Abstract: Liquid crystal elastomers (LCEs) are smart elastomers capable of a reversible shape change triggered by a stimulus such as heat or light. This change in shape is programmed into the material by orienting the mesogen molecules, often through the post-manufacturing alignment of the polymer chains by mechanical stretching. This method limits the possible orientations and necessitates a second curing step to lock the orientation in the structure. Direct ink writing allows for the curing of LCEs directly in an oriented state and for a fine control of the local orientation of the mesogens. The process parameters dictate the actuation and mechanical properties of the 4D-printed object, where time is the fourth dimension. We present in this paper a study of the influence of the printing speed and raster angle on the actuation strain and mechanical properties of the resulting LCE. Complex shape changes can be programmed into specimens that combine variations in printing angles and speeds. We printed two dimensional specimens actuating into helicoids and hinges. Results show the expected influence of printing speed on the level of orientation of the mesogens and on the actuation strain; that is faster printing equals more orientation and actuation strain. The change in raster angle demonstrates the immediate impact of incompatible strains in the structure, as the flat specimen ( i.e. a printed rectangle of a couple of layers thick) actuates in a controlled 3D configuration. Finally, the hinge and helicoid specimens show the versatility of 4D-printed LCE systems, where the folding angle of the hinge or the pitch of the helicoid can be programmed through basic geometry, angle, and speed control at the printing stage. This transformative step in the preparation of LCE actuators opens the door to precise customization exploiting the mobility of mesogens on the polymer chains during printing and the flexibility of the direct ink writing process. Graphical abstract: Highlights: Direct ink writing simultaneously orients and cures the liquid crystal elastomer. We study the influence of printing speed and raster angle on actuation and mechanical properties. Faster printing improves orientation and actuation strain. Incompatible strains lead flat specimens to actuate in a controlled 3D configuration. Hinge folding angle or helicoid pitch can be programmed through geometry, angle, and speed.